Diseño para la implementación de la metodología seis sigma en una línea de producción de queso fresco - Moreano, Annabel (2010)
This thesis project is a guide for the implementation of the Six Sigma Methodology within a manufacturing process. This case was focused on a fresh cheese processing plant. Cheese quality improvement, reduction on unnecessary costs attributable to failure in the process, company profits increase, and teamwork reinforcement among the employees were the different aspects to be enhanced. The methodology, origins, stages, tools, information about the product as well as its manufacturing process are shown along this project. It is complemented with a project development based on gathered data from the cheese manufacturing plant. In order to collect the necessary information different quality and descriptive statistics tools were used; the first ones helped to generate and organize ideas, while the others served to measure variable within the industrial process. During the work progress the variability of the process was determined, and its causes were researched. In addition, diverse solutions were proposed. Six Sigma is a disciplined, data-driven approach and methodology for eliminating defects in any process – from manufacturing to transactional and from product to service. The fundamental objective of the Six Sigma methodology is the implementation of a measurement-based strategy that focuses on process improvement so that companies have a higher quality and, therefore, they can increase their sales, profits and target market.